2016
DOI: 10.1002/adma.201504831
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Controlling Surface Structure to Construct Defect‐Rich Intermetallic Nanocrystals: Effective and Stable Catalysts

Abstract: Kinetic control of surface defects is achieved, and cubic, concave cubic, and defect-rich cubic intermetallic Pt3 Sn nanocrystals are prepared for the electro-oxidation of formic acid. The generality of this kinetic approach is demonstrated by the fabrication of Pt-Mn nanocrystals with different surface defects. The defect-rich nanocrystals exhibit high catalytic activity and stability concurrently, indicating their potential application in fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 43 publications
4
84
1
Order By: Relevance
“…From 2 to 5 h, a slight shift was observed, which can be interpreted by the increased lattice parameter and the grain size increased from 5.2 to 8.1 nm calculated by the Scherrer equation. [16] Since the properties of alloyed CNCs are highly dependent on their compositions, some control experiments have been conducted. In this work, the composition of PtNi alloyed CNCs can be easily varied by adjusting the feeding ratios of the two metal precursors.…”
Section: Resultsmentioning
confidence: 99%
“…From 2 to 5 h, a slight shift was observed, which can be interpreted by the increased lattice parameter and the grain size increased from 5.2 to 8.1 nm calculated by the Scherrer equation. [16] Since the properties of alloyed CNCs are highly dependent on their compositions, some control experiments have been conducted. In this work, the composition of PtNi alloyed CNCs can be easily varied by adjusting the feeding ratios of the two metal precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the chemical composition, the electrocatalytic performance of nanocrystals is strongly dependent on their morphology and structure . Density functional theory calculations indicate that the surface structure of the nanocrystals favors the binding of FAO intermediates, leading to amplified catalytic activity and improved stability .…”
Section: Methodsmentioning
confidence: 99%
“…Density functional theory calculations indicate that the surface structure of the nanocrystals favors the binding of FAO intermediates, leading to amplified catalytic activity and improved stability . Wang and co‐workers demonstrated that constructing surface defects could endow the high catalytic activity of the catalysts while keeping their structure stability . Especially, hollow or porous nanostructures have received unprecedented interests in electrocatalysts for the FAO owing to the high specific surface area and rich surface defects, which contain high density of catalytically active sites .…”
Section: Methodsmentioning
confidence: 99%
“…During electrochemical process, small-size noble metal-based nanocomposites provide high electrocatalytic activity, but the challenge is the aggregation that could happen under electrocatalytic conditions, resulting in the poor performance of long-term stability test (e.g., commercial Pt/C). Alloying one or two kinds of transition metals with noble metal has become a valid strategy to develop excellent electrocatalysts [22][23][24][25]. The addition of the second/third metal not only changes the surface active sites by ensemble effect, but also alters the binding strength of reactants, intermediates, and products by electronic/strain effect [26][27][28].…”
Section: à2mentioning
confidence: 99%
“…Compared with alloy, intermetallic compounds show outstanding structure stability owing to the ordered atom arrangements. Rong et al developed a kinetically controlled method to tune the surface defect of Pt-based intermetallics [24]. Based on their proposed growth mechanism, large electronegativity difference, etching and diffusing processes are necessary for the synthesis of defect-rich cubic intermetallic Pt 3 Sn NCs.…”
Section: Pt-based Alloys and Intermetallicsmentioning
confidence: 99%